Theory and the novel : narrative reflexivity in the British tradition - Williams, Jeffrey, 1958- (Literature, culture, theory ;, 1998)
In Theory and the Novel Jeffrey Williams analyses a range of novels - Tristram Shandy, Joseph Andrews, The Turn of the Screw, Wuthering Heights, Lord Jim, and Heart of Darkness - and shows how narrative technique is never beyond or outside plot. He offers a striking and original contribution to readings of the English novel, as well as to current discussions of theory.